(3af cJGHI GdNHQ GdUMaj fXQjG h YedjG (B/s - (3EHQGgje, EHQGgje CMeOs ((3GdEScfOQjI (B:s (3ecJHI GdeYGQa GdMOjKI ,s, 2005)
(3efgL deOI SfI OQGSjI cGedI(B- (3OQhS fXQjI h YedjI aj GdGYdGe GdJWHjbj Yf GdNHQ GdUMaj aj GdUMa h GdeLdGJ (B- (3ehLg dWdHI GdGYdGe h OQGSi GdUMGaI h GdUMajjf ShGA GdeHJOFjf Gh GdPjf de jJe JOQjHge GdJOQjH GdcGaj ShGA GdfXQj Gh GdYedj(B- (3dWGdHj GdOQGSGJ GdYdjG aj GdUMGaI h GdGYdGe HUaI YGeI h NGUI Yf GdNHQ GdUVMaji HWQjbI YdejI (B-(3fXQjI h YedjI(B- (3GdcJGH eNUU GjVG dGYGOI GdJOQjH ef LOjO ddUMajjf GdeMJQajf h GdghGg (B- (3jJVef JOQjHGJ YedjI h GeKdI hGVMI h GSFdIs
(3HHdjhZQGajG (B: (3U(B.129-130s
Keywords: (3GdCNHGQs; (3GdUMGaIs; (3GdcJGHIs